(untitled) (Journal of the College of Basic Education, 2022)
The present study aims at recognizing the effect of the guidance program by using the techniques of Beck’s theory in decreasing the Hypochondriasis for the elderly people. The sample of the study consisted of (20) old people who suffering Hypochondriasis (males and females). To acheive the goal of the study, the two researchers has built two tools for their study according to Beck’s theory, the two tools are Hypochondriasis scale and the guidance program, after exposing them to experts and analyzing their Psychmetrical properties. The researchers also made use of T-test for testing two independent samples and for a single sample, as well as using Pearson Correlation Coefficient and Cronbach’s Alpha, after analyzing the data, they resulted differences between the medium ranks of the treatment group and the control group in the Hypochondriasis scale in the post test after applying the guidance program on the treatment group The study has resulted several recommendations.